2021
DOI: 10.18231/j.ijmi.2020.022
|View full text |Cite
|
Sign up to set email alerts
|

The road to radiation safety and ALARA: A review

Abstract: The rapid progress of medical and dental science with the invention of various drugs have benefited the mankind. The proper and correct diagnosis of diseases is the primary necessity before the treatment. The different imaging modality plays an important role in clinical diagnosis, teaching and in the field of research. With advent of modern technology in imaging medical imaging has also greatly influenced. A diagnostic radiograph has become a hotspot in diagnosis and the clinical applications. The technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…9 In our study, most of the dentists said that they are not aware of the ALARA principle which is opposite to the study done by Almohaimede AA et al, in 2020. [10][11][12] But like our results, the majority of studies reported a lack of awareness about the ALARA principle as well. A study conducted in Nepal regarding radiation hazards and safety showed that 88% of the participants were aware about it.…”
Section: Discussionsupporting
confidence: 74%
“…9 In our study, most of the dentists said that they are not aware of the ALARA principle which is opposite to the study done by Almohaimede AA et al, in 2020. [10][11][12] But like our results, the majority of studies reported a lack of awareness about the ALARA principle as well. A study conducted in Nepal regarding radiation hazards and safety showed that 88% of the participants were aware about it.…”
Section: Discussionsupporting
confidence: 74%
“…The basic idea in radiation protection is to be exposed to radiation as low as possible. The As Low As Reasonably Achievable (ALARA) principle expresses the necessity of minimizing the dose emitted and exposed from any radioactive source [ 5 , 6 , 7 , 8 ]. It covers a regulation that is not only for safety purposes but also includes the necessary legislative procedures for all radiation protection programs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, applying the radiation protection principles in the use of x-ray beam in the health sector is a mandatory requirement that must be met [8]- [10]. In Indonesia, the use of an x-ray beam machine must have a permit from the Nuclear Energy Regulatory Agency of Indonesia (BAPETEN) and meet the As Low as Reasonably Achievable (ALARA) principle [7], [11]- [14]. One of the efforts to apply radiation dose optimization in diagnostic radiology is using the Diagnostic Reference Level (DRL) [15]- [19].…”
Section: Introductionmentioning
confidence: 99%